Automatic Measurement of Human Body Temperature on Thermal Image Using Knowledge-Based Criteria - Fitriyah, Hurriyatul; Rachmadi, Aditya; Setyawan, Gembong Edhi (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
Instead of thermometer, an infrared camera could be uti-lized to scan body temperature instantly and non-contact. This paperproposed a non-contact measurement of human body temperature by au-tomatically locating inner-chantus on thermal images. The inner-canthuswere detected in both eyes individually. It located inner-canthi based ontemperature where inner-canthi has the highest temperature in face area.A Thresholding based on 9-highest temperature were applied to detectcandidates of inner-canthus' blob as it must have minimum 9 pixel areaaccording to the Standard. Three knowledge based on characteristic ofeye were also applied in the algorithm as several spot in face usuallyfalls within the temperature threshold. The result show accuracy of al-gorithm to detect eye is 82% whether the eyelids were open or closed.There is no signicant dierent of temperature between closed and openeyes based on paired t-test. The algorithm also showed similar result tothermometer measurement based on paired t-test.